Effectiveness of Agility Ladder and Shuttle Run Training on Dribbling Agility in Futsal Games - Maharani, Wida; Muhtar, Tatang; Dinangsit, Dinar (Jurnal Porkes, 2024)
This research aims to determine the differences between agility ladder and shuttle run training for futsal players. The method used in this research is quantitative research. Data collection in this study began by performing zig-zag dribbling movements, and then treatment was given to two groups, namely the agility ladder and shuttle run groups. The population in this study was SDN Bojongsalam 01, totaling 40 students who were also designated as samples. The results of this research show that the agility ladder and shuttle run training methods are good. In this research, students were treated by providing 12 meetings with two groups of 20 students each. Agility ladder and shuttle run exercises are dribbling agility training activities that can be used in this research to improve dribbling agility. This is supported by the data obtained for the increase in the agility ladder group, which has an independent of 0.840, while the increase in the shuttle run has a mean of 0.843, or (0.840 > 0.843). The agility ladder run training can be produced more effectively than the shuttle run in improving futsal dribbling agility at SDN Bojongsalam 01.